LOW-NOISE AXIFUGAL ROTATING HARDENING MACHINERY DESIGN - Mikhail E. Popov; Igor V. Boguslavskiy (Advanced Engineering Research, 2012)
The axifugal rotating hardeni ng machinery construction of the long components is considered. High efficiency in noise abatement in the operating place up to the admissible limit values is shown.